Generation of integration-free human iPSC line LCPHi001-A from a Parkinson's disease patient carrying the RecNciI mutation in GBA gene - Xianjie Lu; Na Song; Wei Wang; Yanming Liu; Hao Song; Li Xu; Yan Wang; Chuanfei Wei; Juanli Chen; Xiaofei Yang; Fabin Han (Stem Cell Research, 2021)
Parkinson’s disease (PD) is a neurodegenerative disease caused by environmental and genetic factors. The identified PD genes include SNCA, LRRK2, Parkin, DJ-1, PINK1, and ATP13A2. Mutations in the glucocerebrosidase (GBA) gene were reported to be associated with PD in different ethnic populations. Here we generated a novel induced pluripotent stem cell (iPSC) line LCPHi001-A from a PD patient carrying RecNciI mutation (c.1448 T > C, c.1483G > C, and c.1497G > C) in GBA by non-integrative episomal plasmids. The LCPHi001-A line expressed pluripotency markers, displayed differentiation capacity to three germ layers in vivo, and had the normal karyotype.